MENEMUKAN KEMBALI RUMUS LUAS PERSEGI PANJANG DENGAN KONSTRUKTIVISME (STUDI KASUS PADA MAHASISWA PGSD) - Isrok’atun, Isrok'atun (Universitas Pendidikan Indonesia, 2015)
A knowledge is the result from students' self-construction idea, which makes more meaning full of learning process. Sometimes, teachers forget to elicit students’ life experience as their prior knowledge. If this prior knowledge exposed, student will be easily received the new idea, because the students indirectly build their own knowledge. The constructivism point of learning is a teaching and learning process in such a way will make students are mentally active in construct their own knowledge, based on their cognitive structure. It must be considered how the children forming their concept in cognitive structure as the acquisition in geometry concepts. Knowing of the geometry formulas is not a guarantee that the student has thoroughly been learning about the geometry concept. On the other hand, the formula of rectangles’ area is not come instantly, but it can be reformulated by the construction of students’ prior knowledge. I brought them in a specific activity that makes them enjoy and vigorously; students are directed to find a rectangles’ formula.Keywords: constructivism, build knowledge, discovery, and rectangular formula.